Facebook como plataforma digital y su incidencia en la comunicación errónea de los habitantes del cantón Quevedo, año 2022 - Kaiser Rodríguez, Alfredo Joel (2022)
The purpose of this research is to analyze the use of Facebook as a digital platform to measure the incidence of erroneous communication of the inhabitants of the Quevedo canton, throughout history the human being has created forms and means of communication, according to the account of the history from pictograms, smoke signals etc.,at present there are digital media that allow real-time communication of any type of event worldwide, it is for this reason that most human beings use digital platforms as a means of informative communication , Of course, not everything that is on digital platforms can be true, and the incidence of fake news on the internet is quite high, so much so that Facebook is one of the most used platforms for the publication of this type of content, the incorrect way of manipulating this type of content has created a controversy where it casts doubt on whether the content is real or false, creating desinformation in the population of Quevedo, who are not aware of the veracity or not of this type of publication, for this reason it is intended to analyze the possible causes in this population that has led to erroneous communication, because through the observation of several news pages and groups found on the social network Facebook, the duplicity of official pages with false news circulating in the city of Quevedo has been identified.